Juridical analysis of the obligation to report drug offenders to law enforcement officials law enforcement - Ady Satrio Gustian; Soerya Respationo; Erniyanti Erniyanti; Darwis Anatami; Parameshwara Parameshwara (Goodwood Publishing, 2022)
Purpose: The purpose of this study is to determine the legal regulation of the obligation to report the perpetrators of criminal acts of narcotics users, to determine the implementation of the obligation to report the perpetrators of criminal acts of narcotics users to law enforcement officials. Research Methodology: The research method used is normative juridical (legal reasearch) through literature study with an empirical juridical approach (sociological juridical) through field studies aimed at obtaining legal knowledge empirically. Results: The results showed that the legal regulation of the obligation to report the perpetrators of criminal acts of narcotics use is regulated in Article 103 and Article 104 of Law Number 35 of 2009 concerning Narcotics which states that everyone who knows that there is a criminal act of abuse and illicit drug trafficking is obliged to report it to investigators or other authorized officials. Contribution: Despite these limitations, the obligation to report drug offenders can make a significant contribution to society. By reporting drug offenders, individuals can help to reduce crime, protect public health, and promote justice. Implementation: The implementation of the obligation to report the perpetrators of criminal acts of narcotics use to law enforcement officials in Bintan, Riau Islands has not been running optimally because the role of the community in reporting the perpetrators has not been implemented properly due to the lack of public awareness and education regarding the legal implications of narcotics use, thus hindering community participation in the reporting process.